Melukis Dengan Cahaya Melalui Kamera Lubang Jarum (KLJ) - Andry Prasetya (Ornamen, 2005)
Â From existing simple materials around us, we can get some discourse aspect in photography growth that happened continuesl. The technological growth specially photography represent the innovation from previous invention. Principal development work the photography â€œpaint with the lightâ€ and,â€.. ..the light Â makeÂ  a move to through the straight line and an obyect will bounce the ray to all angle â€œ, ProgressivÃ«ly find its existence as according to epoch growth. To the last created by a sophisticated camera which many we meet in this time, principal its activity as according to camera pinhole, what in Indonesia can be called with the Camera of Needle Hole (KLJ) started from 25 century ago.Â The Process of create the picture started from determination of object field continued with the irradiating and ending with amazing process, if we see the process Â of image appearance from laminated paper of emulsion illuminated to enrich the in doing photographic activities.keyword :the light, camera, needle hole, photographic activities